2022
DOI: 10.3389/fpsyg.2022.977931
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of achievement emotions on online learning outcomes: A systematic review

Abstract: Recently, achievement emotions have attracted much scholarly attention since these emotions could play a pivotal role in online learning outcomes. Despite the importance of achievement emotions in online education, very few studies have been committed to a systematic review of their effects on online learning outcomes. This study aimed to systematically review studies examining the effects of achievement emotions on online learning outcomes in terms of motivation, performance, satisfaction, engagement, and ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…From a theoretical standpoint, this study shows the complex role that achievement emotions play in the interplay between goal orientations, motivational components and academic achievement. However, it is still to determine the effects of negative achievement emotions ( Wu and Yu, 2022 ). We found that self-efficacy is the only mediator that explained the relationship between goal orientation and achievement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a theoretical standpoint, this study shows the complex role that achievement emotions play in the interplay between goal orientations, motivational components and academic achievement. However, it is still to determine the effects of negative achievement emotions ( Wu and Yu, 2022 ). We found that self-efficacy is the only mediator that explained the relationship between goal orientation and achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Positive activating emotions can positively influence performance, by increasing motivation and stimulating flexible learning, while negative deactivating emotions can affect performance by diminishing motivation, distracting attention and superficial solving of tasks ( Pekrun et al, 2002 ; Pekrun et al, 2009 ; Muis et al, 2015 ). A recent systematic review suggest positive achievement emotions in online learning contexts may be much more effective than negative ones in improving learners’ motivation, performance and achievement, but in the same time negative activating emotions, such as anxiety and frustration, also positively influence performance of subjects ( Wu and Yu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 84% of college students reported that some or all classes were moved to online-only instruction [69]. Previous research has discovered an association between emotions and distance education [70][71][72][73]. For example, Pirrone et al [74] found that online instruction led to a decrease in anxiety.…”
Section: Online Educationmentioning
confidence: 99%
“…The effects of especially positive deactivating and negative activating emotions on learning are complex ( Pekrun and Linnenbrink-Garcia, 2014 ). Experiencing positive deactivating emotions (e.g., relaxation) can reduce students’ effort and negatively influence learning, contrary to positive activating emotions (e.g., enjoyment and pride) ( Wu and Yu, 2022 ). Negative activating emotions (e.g., frustration and anxiety) are shown to impede learning, but can also enhance students’ effort to perform better ( Graesser and D’Mello, 2012 ; Pekrun, 2017 ; Cloude et al, 2021 ; Taub et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%